136k views
10 votes
How do I solve this 2 step equationn?
y/6 - 7 = 4

User Mike Finch
by
5.0k points

2 Answers

7 votes

Answer: by isolating the variable

Explanation:

Y/6 -7=4

Y/6-7+7=4+7

Y/6=11

Y/6*6=11*6

Y=66

User Michael Pasqualone
by
4.9k points
6 votes

Answer: y= 66

Step-by-step explanation: Well first you would do +7 on both sides and then it would be Y/6=4+7, then you would multiply 6 on both sides which then you would have y=24+42 which simplified it would be y=66

User Dizarray
by
4.6k points